Caracterização de parques lineares: o Eco Parque Morumbi como referência na cidade de Cascavel-PR. - Camargo, Juliane Rodrigues de Almeida (2020)
The conservation of permanent preservation areas is key for the proper urban development of a city, once these areas play an important role regarding the conservation of water resources, as well as the preservation of the fauna and flora of urban and rural ecosystems. However, the inappropriate urban planning during the expansion associated to the neglect of the population in general impacts adversely this area, which should be preserved not only for this generation, but also for the next ones. Free urban spaces in native regions emerge as an alternative in the creation of social integration, and as an area where the awareness of the preservation of the environment is built by the population. The objective of this study is to analyse which characteristics and elements underlie a linear park, in a way that it contributes to the management of valley floor areas, using Morumbi Ecopark in the city of Cascavel, in Paraná state, as reference. The methodology used in this work has a qualitative research approach in which bibliographic review, documentary analysis and case study were made. This study was divided in three steps: the diagnosis of the study area through photographic survey of the pre-implementation stage, data survey through thematic maps, projects and documents granted by public agencies. In the second stage, the content analysis technique based on the interpretation of the collected data, what are their main similarities and differences, pointing out and discussing the negative and positive aspects for the implementation of linear parks as a strategy for the environmental recovery. In the third stage of this study, pictures were collected and an on-site visit was made in the Morumbi Ecopark, which are available for the population of the North Region of the city. The results obtained in this research showed the necessity of preserving the water resources, and the preservation of the fauna and flora, or their recovery. Therefore, this research sought to emphasise the importance of preserving environmental areas, and how these factors influence the recovery of the Amabay streamlet and its riparian forest, as well as emphasise in what ways the implementation of a urban linear park can influence the environmental and social dynamics of the North Region of the city of Cascavel.